2019
DOI: 10.1016/j.ypmed.2018.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Foreclosures and weight gain: Differential associations by longer neighborhood exposure

Abstract: While home foreclosure can lead to mental and physical health declines in persons experiencing the foreclosure, whether neighborhood foreclosures can affect the health of other residents is debatable. Using a racially/ethnically diverse sample of Chicago metropolitan area residents linked to foreclosure data from 2008 to 2014, we assessed whether exposure to neighborhood foreclosure fillings was associated with changes in objectively measured body mass index (BMI) over time. Using a retrospective longitudinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Multiple studies suggest that foreclosures impact the wellbeing of families directly affected through financial distress and access to health care (Currie and Tekin, 2015; Pollack and Lynch, 2009). Further, foreclosures may have second-order impacts on families in neighboring households, through stress related to their own economic stability (Arcaya et al, 2014, 2013; Currie and Tekin, 2015; Duran et al, 2018; Houle and Light, 2014) and deterioration of the community and neighborhood physical environment (Cohen et al, 2003; Kelling and Wilson, 1982). However, few studies (Duran et al, 2018) have not addressed recent calls to examine how foreclosure recovery (or lack thereof) has affected health (Arcaya, 2017; Duncan and Kawachi, 2018), and none has assessed the potential influence of historical measures of housing discrimination on current foreclosures and health.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies suggest that foreclosures impact the wellbeing of families directly affected through financial distress and access to health care (Currie and Tekin, 2015; Pollack and Lynch, 2009). Further, foreclosures may have second-order impacts on families in neighboring households, through stress related to their own economic stability (Arcaya et al, 2014, 2013; Currie and Tekin, 2015; Duran et al, 2018; Houle and Light, 2014) and deterioration of the community and neighborhood physical environment (Cohen et al, 2003; Kelling and Wilson, 1982). However, few studies (Duran et al, 2018) have not addressed recent calls to examine how foreclosure recovery (or lack thereof) has affected health (Arcaya, 2017; Duncan and Kawachi, 2018), and none has assessed the potential influence of historical measures of housing discrimination on current foreclosures and health.…”
mentioning
confidence: 99%
“…Further, foreclosures may have second-order impacts on families in neighboring households, through stress related to their own economic stability (Arcaya et al, 2014, 2013; Currie and Tekin, 2015; Duran et al, 2018; Houle and Light, 2014) and deterioration of the community and neighborhood physical environment (Cohen et al, 2003; Kelling and Wilson, 1982). However, few studies (Duran et al, 2018) have not addressed recent calls to examine how foreclosure recovery (or lack thereof) has affected health (Arcaya, 2017; Duncan and Kawachi, 2018), and none has assessed the potential influence of historical measures of housing discrimination on current foreclosures and health. In the present paper, we examined the association between recent changes in neighborhood-level foreclosure rate and self-rated health among Detroit residents at both the neighborhood and individual levels, and estimated the confounding bias introduced by excluding historical redlining practices in models estimating these associations.…”
mentioning
confidence: 99%
“…Authors found that each additional foreclosed property located within 100 m of a person’s home occurring in the year preceding the study examination was associated with a 0.2 kg/m 2 increase in BMI and a 1.77 higher odds of being overweight (95% CI 1.02, 3.05) [ 80 ]. A cohort study of 59,854 adults receiving care at a Veterans Health Administration (VA) facility in metropolitan Chicago found no association between neighborhood foreclosures and BMI over six years of follow-up in the overall sample; however when restricting the sample to people who did not move over the study period, authors found that every 20 additional foreclosures was associated with a 0.03 kg/m 2 increase in BMI (95% CI 0.01, 0.06) [ 86 ]. In contrast, a study of 105,919 continuously insured adults with diabetes in Northern California did not find an association between census-level foreclosure and BMI, though authors noted that the relatively shorter study period of four years may not have been long enough to detect an effect [ 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…To date, a variety of community‐level economic indicators (e.g., unemployment) have been linked to higher obesity prevalence at the national level in several cross‐sectional studies . Economic conditions at state and county levels may influence changes in adult BMI levels through losses in earned income and constraints on household food budgets , though some evidence has suggested that extreme forms of economic hardship (e.g., foreclosures) may contribute to food insecurity and decrease obesity risk . Furthermore, prior research has suggested that low‐income individuals are often exposed to the poorest‐quality environments (e.g., poor neighborhood and housing conditions, low street connectivity, lack of safety and social cohesion) , which may contribute to socioeconomic disparities in BMI levels.…”
Section: Introductionmentioning
confidence: 99%